Overview: Bellagio Conference on Program and Policy Options for Preventing Obesity in the Low‐ and Middle‐Income Countries. (23rd October 2013) - Popkin, B.; Monteiro, C.; Swinburn, B.
Summary: The Bellagio 'Conference on Program and Policy Options for Preventing Obesity in the Low‐ and Middle‐Income Countries' (LMICs) was organized to pull together the current. We need not reiterate the importance of this topic or the speed of change in eating, drinking and moving facing us across the globe. The conference emerges from need to significantly step up the policies and programs to reduce obesity by learning from some current examples of best practice and strengthening the role of the academic and civil society players in translating global evidence and experience into action at the national level. There is also a need to empower the younger generation of scholars and activists in these countries to carry on this effort. The meeting was also timely because a number of funding agencies in the United States, Canada and the UK, at least, are beginning to focus attention on this topic. This set of papers provides not only examples of existing best practice but also a road map ahead for LMICs in the various areas of action needed to reduce obesity across LMICs. The meeting highlighted critical barriers to implementation that have blocked many initiatives.